Decoding TGR5: A comprehensive review of its impact on cerebral diseases - Zehan Zhang; Yifei Zhang; Hongye Peng; Qingqian Yu; Xiangdong Kang; Ying Liu; Yuxiao Zheng; Fafeng Cheng; Xueqian Wang; Feng Li (Pharmacological Research)
Currently, unraveling the enigmatic realm of drug targets for cerebral disorders poses a formidable challenge. Takeda G protein-coupled receptor 5 (TGR5), also known as G protein-coupled bile acid receptor 1, is a specific bile acid receptor. Widely distributed across various tissues, TGR5 orchestrates a myriad of biological functions encompassing inflammation, energy metabolism, fatty acid metabolism, immune responses, cellular proliferation, apoptosis, and beyond. Alongside its well-documented implications in liver diseases, obesity, type 2 diabetes, tumors, and cardiovascular diseases, a growing body of evidence accentuates the pivotal role of TGR5 in cerebral diseases. Thus, this comprehensive review aimed to scrutinize the current insights into the pathological mechanisms involving TGR5 in cerebral diseases, while contemplating its potential as a promising therapeutic target for cerebral diseases.